Investment opportunity of blockchain technology in the education sector of Saudi Arabia: A systematic literature review - Alshareef, Nasser (Frontiers in Education, 2022)
The primary objective of this research is to explore the literature on blockchain technology and its investment opportunity in the education sector. Studies on the investment opportunities of blockchain technology in education have remained limited and little is known about the existing state of knowledge and practice of blockchain technology in the education sector of Saudi Arabia, especially for its sustainable development. In this study, the author tried to synthesize literature on blockchain technology to understand the difficulties and prospects of this technology in Saudi Arabia. A total of 15 empirical studies from 2017 to 2020 were reviewed. The descriptive and thematic analysis identified four types of challenges of blockchain technology in the education sector. They include leaking privacy and security, processing cost, setting the boundaries, and weakening school credentials. The review also revealed several opportunities for adopting blockchain technology such as certifying identity authentication, improving learning assessment, maintaining student records, enhancing trust, and reducing costs. Implications and recommendations related to education for sustainable development are provided accordingly.